Reaction mechanisms of metal complexes - Hay, R. W. (Horwood, 2000)
Annotation This text provides a general background as a course module in the area of inorganic reaction mechanisms, suitable for advanced undergraduate and postgraduate study and/or research. The topic has important research applications in the metallurgical industry and is of interest in the science of biochemistry, biology, organic, inorganic and bioinorganic chemistry. In addition to coverage of substitution reactions in four-, five- and six-coordinate complexes, the book contains further chapters devoted to isomerization and racemization reactions, to the general field of redox reactions, and to the reactions of coordinated ligands. It is relevant in other fields such as organic, bioinorganic and biological chemistry, providing a bridge to organic reaction mechanisms. The book also contains a chapter on the kinetic background to the subject with many illustrative examples which should prove useful to those beginning research.
Includes index.
Keywords: Metal complexes.; Reaction mechanisms (Chemistry); elektronické knihy; electronic books